2020
DOI: 10.2147/ott.s273527
|View full text |Cite
|
Sign up to set email alerts
|

<p>Local Delivery of Minocycline and Vorinostat Targets the Tumor Microenvironment to Inhibit the Recurrence of Glioma</p>

Abstract: Background: Postoperative recurrence is the main reason for poor clinical outcomes in glioma patients, so preventing tumor recurrence is crucial in the management of gliomas. Methods: In this study, the expression of matrix metalloproteinases (MMPs) in normal tissues was detected via RNA-seq analysis. Glioma cases from the public databases (The Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA)) were included in this study. The hydrogel contains minocycline (Mino) and vorinostat (Vor) (G/Mino+V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Literature relating to using GelMA to deliver MH has been mostly on direct mixing [38,39], our findings indicate that this approach results in high burst release and lacks sustained-release properties. In addition, the significantly reduced accumulative release from direct mixing groups may account for the oxidation from free radicals residuals of GelMA photocrosslinking.…”
Section: Controlled Release Of Mh From Mh-ds Nanocomplexes In Gelmamentioning
confidence: 81%
“…Literature relating to using GelMA to deliver MH has been mostly on direct mixing [38,39], our findings indicate that this approach results in high burst release and lacks sustained-release properties. In addition, the significantly reduced accumulative release from direct mixing groups may account for the oxidation from free radicals residuals of GelMA photocrosslinking.…”
Section: Controlled Release Of Mh From Mh-ds Nanocomplexes In Gelmamentioning
confidence: 81%
“…Many epigenetic modifications occur in glioma resulting in substantial molecular heterogeneity that confers advantages for tumor development (Phillips et al, 2020 ). Among the enzymes involved, the histone deacetylases regulate different hallmarks of glioma pathogenesis, such as proliferation, invasiveness, and formation of new vessels (Pastorino et al, 2019 ; Zhao et al, 2020 ). HDACi fascinated researchers in almost all fields of cancer biology: five of them have been approved by FDA for clinical use and many others tentered clinical trials as single agents or in combination therapy for a variety of cancer diseases (Ecker et al, 2013 ; Lee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local Delivery of vorinostat can alter the tumor microenvironment, thereby inhibiting glioma recurrence (40). Vorinostat can also mediate the regulation of cell cycle regulatory proteins in glioma (41).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that vorinostat combined with Bevacizumab or Temozolomide can be used in the treatment of glioma ( 33 35 ), as well recurrent malignant gliomas ( 36 39 ). Local Delivery of vorinostat can alter the tumor microenvironment, thereby inhibiting glioma recurrence ( 40 ). Vorinostat can also mediate the regulation of cell cycle regulatory proteins in glioma ( 41 ).…”
Section: Discussionmentioning
confidence: 99%